2016
DOI: 10.21037/jtd.2016.04.37
|View full text |Cite
|
Sign up to set email alerts
|

Why a second look might be worth it: immuno-modulatory therapies in the critically ill patient

Abstract: Sepsis and septic shock are associated with high mortality rates and remain a serious menace for the critically ill patient. Concurrent activation of pro-and anti-inflammatory pathways and an excessive cytokine release represent initial key features in the deregulation of the humoral and cellular antimicrobial defense. Research of the last decades addressed both the ebullient inflammation as well as the resulting longterm failure of the host immunity. While the reestablishment of an adequate immune-competence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…In accordance with the literature [ 17 , 18 ], endotoxemia in the present model was characterized by cardiovascular and hemodynamic impairment. In addition, we demonstrated that injecting LPS in rodents produces a pronounced systemic inflammatory reaction in the form of markedly increased expression and concentration of proinflammatory cytokines, as also shown previously by other studies [ 19 , 20 , 21 , 22 ].…”
Section: Discussionsupporting
confidence: 89%
“…In accordance with the literature [ 17 , 18 ], endotoxemia in the present model was characterized by cardiovascular and hemodynamic impairment. In addition, we demonstrated that injecting LPS in rodents produces a pronounced systemic inflammatory reaction in the form of markedly increased expression and concentration of proinflammatory cytokines, as also shown previously by other studies [ 19 , 20 , 21 , 22 ].…”
Section: Discussionsupporting
confidence: 89%
“…However, further studies are required to validate the use of theophylline for the treatment of sepsis. Future studies should investigate epigenetic heterogeneity and explore strategies to avoid potentially harmful effects of candidate drugs such as theophylline [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Blocking systemic inflammation by targeting specific cytokines through antibody-mediated neutralization have so far yielded mixed results in clinical settings [135][136][137][138] or effectiveness in selected subgroups.…”
Section: Covid-19 For Avenues Therapeuticmentioning
confidence: 99%